A New Measure of Interpersonal Exploitativeness - Brunell, Amy B.; Davis, Mark; Schley, Dan R.; Eng, Abbey; van Dulmen, Manfred; Wester, Kelly; Flannery, Daniel (Frontiers in Psychology, 2013)
Measures of exploitativeness evidence problems with validity and reliability. The present set of studies assessed a new measure [the Interpersonal Exploitativeness Scale (IES)] that defines exploitativeness in terms of reciprocity. In Studies 1 and 2, 33 items were administered to participants. Exploratory and Confirmatory Factor Analysis demonstrated that a single factor consisting of six items adequately assess interpersonal exploitativeness. Study 3 results revealed that the IES was positively associated with “normal” narcissism, pathological narcissism, psychological entitlement, and negative reciprocity and negatively correlated with positive reciprocity. In Study 4, participants competed in a commons dilemma. Those who scored higher on the IES were more likely to harvest a greater share of resources over time, even while controlling for other relevant variables, such as entitlement. Together, these studies show the IES to be a valid and reliable measure of interpersonal exploitativeness. The authors discuss the implications of these studies.